KHALIMA NASIROVA - AT THE UZBEK NATIONAL OPERA ART - Muyassarkhan Achildieva; Farangis Ikromova (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
The article provides information on the work of Halima Nosirova, a bright representative of the Uzbek national opera art. Opinions and comments on the art of Uzbek opera are reflected in the article.